Innovation In Arabic Language Learning Programs at SMPI Yambu’ul Qur’an Kediri Indonesia - Nabila An'imatul Maula; Muhamad Khozin; Ahmat Saifudin; Moh. Ghundar Najih; Nazih Hibatullah Muhammad (Jurusan Pendidikan Bahasa Arab UIN Kiai Ageng Muhammad Besari onorogo, 2026)
Arabic language learning in the modern era is expected not only to emphasize the mastery of linguistic rules but also to foster students' communicative competence. One of the approaches considered relevant to achieving this objective is Communicative Language Teaching (CLT), which emphasizes the use of language in authentic communicative contexts. This study aims to analyze the innovation of Arabic language learning programs at SMPI Yambu'ul Qur'an (YAQU) Kediri from the perspective of Communicative Language Teaching (CLT). The study employed a qualitative approach using a case study design. Data were collected through observations, interviews, and documentation, and were analyzed using data reduction, data display, and conclusion drawing techniques. The findings reveal that the innovations in Arabic language learning are implemented through three main programs: muhadatsah (Arabic conversation) habituation, film-based learning, and Arabic debate activities. From the perspective of CLT, these programs reflect the principles of communicative language teaching by providing students with opportunities to use Arabic in authentic communicative situations, promoting learner interaction, encouraging student-centered learning, and developing communicative competence, including listening and speaking skills, vocabulary mastery, critical thinking, and self-confidence. The study concludes that the implementation of learning innovations aligned with CLT principles creates a communicative learning environment and contributes significantly to improving the quality of Arabic language learning at the school.